Three Basic Types of Temperaments - Diana Converse (EDIS, 2009)
FAR0075, a 2-page transcript of the Family Album Radio Program broadcast by Diana Converse, describes three basic types of temperaments identified by child development experts to as patterns of behavior determined at birth. Published by the UF Department of Family Youth and Community Sciences, March 2009.